Research on interface mechanical behavior of composite coatings on surface of uranium components - SHI PingAn; WANG TianZhong (Jixie qiangdu)
Aiming at the problem of low interfacial combination strength or even cracking properties of composite coatings on uranium surface, based on the research of interface characteristics of composite coatings, the numerical model was established to study the interface mechanical behavior of coating interface, and effects of deposition temperature, coating material and component size on interfacial mechanical behavior of Al/Ti, Al/Al2O3 composite coatings were discussed. The results indicate that the stress-oscillation behavior occur at the interface of out coating when the deposition temperature exceeds 300 ℃, and which will directly affect the interfacial bonding strength of the composite coatings. Therefore, the deposition temperature of Al/Ti, Al/Al2O3, composite coatings must not exceed 300 ℃ during magnetron sputtering deposition process. Compared with Al/Ti composite coatings, Al/Al2O3 composite coatings can not only improve the adhesion of Al coating and uranium substrate, but also reduce the stress-oscillation at the interface, which will be the main research directions to further improve the corrosion resistance and wear resistance of uranium and uranium alloys.